Governing sustainable school to work transitions: Can Germany learn from Denmark? - Günther Schmid; Janine Leschke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2025)
In international comparison, dual systems of vocational education and training are often considered to be more successful than school-based systems for managing sustainable transitions from school to work. This assessment is particularly valid for Switzerland, while the German dual system has increasingly come under criticism since the Covid-19 pandemic, especially with regard to the declining attractiveness of its vocational tracks. The comparative focus is rarely put on Denmark with its promising mix of both principles. A comparison of the two countries therefore seems appealing. The study starts by developing the theoretical framework of transitional labour markets: normatively, it stresses professional sovereignty against labour market fitness, while analytically, it emphasises fair risk and balanced power sharing as principles of good governance. It then considers the actors, regulations, transition paths, current developments and problems of the two countries, enriched with descriptive statistics. Germany can learn from Denmark, especially regarding early career orientation in school, income security that encourages risk-taking during the complex transition process, the continuous updating and modularisation of curricula, and adaptive cooperation between schools, companies, social partners and municipalities. The weaknesses of the Danish system, however, provide also lessons, especially the erosion of the attractiveness of vocational education and training. Reform options for Germany conclude the study. – – Duale Systeme der Berufsausbildung werden im internationalen Vergleich oft erfolgreicher eingeschätzt als schulische Systeme, den Übergang von der Schule in den Beruf nachhaltig zu gestalten. Diese Einschätzung gilt insbesondere für die Schweiz, während das deutsche System seit der COVID-19-Pandemie zunehmend kritisiert wird, vor allen die sinkende Attraktivität der beruflichen Bildungsgänge. Selten wird der vergleichende Blick auf Dänemark gerichtet, das auf den ersten Blick eine vielversprechende Mischung beider Prinzipien aufweist. Ein Vergleich der beiden Länder erscheint deshalb reizvoll. Die Studie entwickelt zunächst den theoretischen Bezugsrahmen von Übergangsarbeitsmärkten: normativ stellt er die berufliche Souveränität gegenüber der Arbeitsmarkttauglichkeit in den Vordergrund, analytisch betont er faire Risikoteilung und ausgewogene Machtteilung als Grundsätze guter Regierungsführung. Anschließend werden die jeweiligen Akteure, Regelungen, Übergangspfade, aktuellen Entwicklungen und Probleme der beiden Länder vorgestellt, angereichert mit deskriptiver Statistik. Deutschland kann von Dänemark lernen, insbesondere hinsichtlich der frühen Berufsorientierung in der Schule, der Einkommenssicherheit zur Ermutigung der Risikobereitschaft während des komplexen Übergangsprozesses, der kontinuierlichen Aktualisierung und Modularisierung von Lehrplänen und enge Zusammenarbeit zwischen Schulen, Unternehmen, Sozialpartnern und Kommunen. Doch auch aus den Schwächen des dänischen Systems lassen sich Lehren ziehen, insbesondere bezüglich der schwindenden Attraktivität der Berufsbildung. Optionen für Reformen in Deutschland beschließen die Studie.
Keywords: 300; vocational education and training; apprenticeship system; transitions; transitional labour markets; comparative analysis; governance; risk sharing; Berufliche Bildung; Lehrlingssystem; Übergänge; Übergangsarbeitsmärkte; vergleichende Analyse; Risikoteilung